Draft Annual Plan 2012-13 Government of Arunachal Pradesh - Planning Commission (Planning Commission, 2012)
Arunachal Pradesh with a geographical area of 83,743 sq. km is the sentinel of North Eastern border of the country. The State constitutes 2.55 per cent of India’s total geographical area and 31.94 per cent of the North east. The State is topographically, climatically and culturally distinct from rest of the country. It is characterized by varied habitats, heavy rainfall, extremely rich bio-diversity, mountains and hillocks marked by lateral valleys in the north and transverse valleys in the south, dissected by brooks and majestic rivers.
Government of Arunachal Pradesh, Department of Planning